Physical modalities inducing immunogenic tumor cell death for cancer immunotherapy - Adkins, Irena; Fucikova, Jitka; Garg, Abhishek D; Agostinis, Patrizia; Špíšek, Radek (Oncoimmunology, 2014)
The concept of immunogenic cancer cell death (ICD), as originally observed during the treatment with several chemotherapeutics or ionizing irradiation, has revolutionized the view on the development of new anticancer therapies. ICD is defined by endoplasmic reticulum (ER) stress response, reactive oxygen species (ROS) generation, emission of danger-associated molecular patterns and induction of antitumor immunity. Here we describe known and emerging cancer cell death-inducing physical modalities, such as ionizing irradiation, ultraviolet C light, Photodynamic Therapy (PDT) with Hypericin, high hydrostatic pressure (HHP) and hyperthermia (HT), which have been shown to elicit effective antitumor immunity. We discuss the evidence of ICD induced by these modalities in cancer patients together with their applicability in immunotherapeutic protocols and anticancer vaccine development.
Keywords: TLR, Toll-like receptor; HT, hyperthermia; ionizing irradiation; IFNγ, interferon-γ; CRT, calreticulin; EGFR, endothelial growth factor receptor; ROS, reactive oxygen species; Hyp-PDT, Hypericin-based Photodynamic therapy; cancer immunotherapy; HHP, high hydrostatic pressure, HMGB1, high-mobility group box 1; UVC, ultraviolet C light; DC, dendritic cells; ATP, Adenosine triphosphate; HSP, heat shock protein; ER, endoplasmic reticulum; photodynamic therapy with hypericin; immunogenic cell death; high hydrostatic pressure; DAMPs, danger-associated molecular patterns; NDV, Newcastle Disease Virus; RT, radiotherapy; hyperthermia; ICD, immunogenic cell death; eIF2α, eukaryotic translation initiation factor 2α